2000
DOI: 10.1108/07378830010360437
|View full text |Cite
|
Sign up to set email alerts
|

IT developments in Eastern and Southern Africa: implications for university libraries

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Among the personal barriers are the low level of awareness, lack of training or only basic training, limited skills, computer illiteracy and improper marketing. These findings concur with the results of Akporhonor and Akpojotor (2016), Ingutia-Oyieke and Dick (2010), MacMillan (2009), Manda (2005), Mutula (2000) and Odero-Musakali and Mutula (2007). The absence of physical barriers affecting the use of ERs is evident in the fact that the South African Government is investing through the Department of Higher Education in the acquisition of ICTs and ERs and in improving bandwidth and connectivity at universities.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Among the personal barriers are the low level of awareness, lack of training or only basic training, limited skills, computer illiteracy and improper marketing. These findings concur with the results of Akporhonor and Akpojotor (2016), Ingutia-Oyieke and Dick (2010), MacMillan (2009), Manda (2005), Mutula (2000) and Odero-Musakali and Mutula (2007). The absence of physical barriers affecting the use of ERs is evident in the fact that the South African Government is investing through the Department of Higher Education in the acquisition of ICTs and ERs and in improving bandwidth and connectivity at universities.…”
Section: Resultssupporting
confidence: 88%
“…Among which are a lack of awareness, information illiteracy, lack of skills, low bandwidth and ICT challenges. Simply put, physical and personal barriers are the two major obstacles to the use of ERs in most of these universities (Akporhonor and Akpojotor, 2016; Ingutia-Oyieke and Dick, 2010; MacMillan, 2009; Manda, 2005; Mutula, 2000; Odero-Musakali and Mutula, 2007). Physical barriers relate to inadequate infrastructure networks, such as intranets and the internet; lack of native-language content; software power outages; and restricted access to ICT facilities, especially the internet.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rapid and continuing evolution of information technology has occasioned large stocks of electronic resources in libraries and created pressure for both library professionals and users to continue learning in order to provide effective service and make adequate use of the new information materials (Mutula, 2000). In the present study, it was found that 9 percent of respondents replied affirmatively saying that they have undergone formal course for educating the users and 74 percent said that did not undergo any educating course.…”
Section: Discussionmentioning
confidence: 99%
“…South Africa has several vendors of several systems such as STYLIS, ITS, URICA, ERUDITE and small library systems suitable for schools such as Libwin, Papyrus, etc. (Mutula, 2000b). On the other hand, the use of consortia to automate library functions has become increasing popular especially in each of the South Africa's nine provinces.…”
Section: Library Automation Environment In Africamentioning
confidence: 99%